2022
DOI: 10.3390/jof9010046
|View full text |Cite
|
Sign up to set email alerts
|

Sterile Cerebrospinal Fluid Culture at Cryptococcal Meningitis Diagnosis Is Associated with High Mortality

Abstract: Cryptococcus is the leading cause of AIDS-related meningitis in sub-Saharan Africa. The clinical implications of a sterile cerebrospinal fluid (CSF) culture among individuals diagnosed with cryptococcal meningitis using CSF cryptococcal antigen (CrAg) are unclear. We prospectively enrolled 765 HIV-positive Ugandans with first-episode cryptococcal meningitis from November 2010 to May 2017. All persons were treated with amphotericin-based induction therapy. We grouped participants by tertile of baseline CSF quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…(2) The relationship between sterile CSF culture and mortality is still controversial. Although rapid clearance of CSF Cryptococcus is associated with a high survival rate, some studies also indicated that high sterile culture rate was not associated with a low survival rate of patients 33,34 and was even associated with high mortality 35 . Notably, AIDS patients had a trend of high 90‐day mortality compared with CM patients without predisposing disease and non‐AIDS patients with other predisposing disease although no statistical significance was found (log‐rank p = .174).…”
Section: Discussionmentioning
confidence: 99%
“…(2) The relationship between sterile CSF culture and mortality is still controversial. Although rapid clearance of CSF Cryptococcus is associated with a high survival rate, some studies also indicated that high sterile culture rate was not associated with a low survival rate of patients 33,34 and was even associated with high mortality 35 . Notably, AIDS patients had a trend of high 90‐day mortality compared with CM patients without predisposing disease and non‐AIDS patients with other predisposing disease although no statistical significance was found (log‐rank p = .174).…”
Section: Discussionmentioning
confidence: 99%
“…Host damage may occur as a result of tissue invasion due to inadequate defences, or due to a poorly regulated and overly exuberant response (Fig. 2) [11 ▪ ,12]. Patients susceptible to IFRI often have broad immunological deficits, such as severe combined immunodeficiency [13].…”
Section: The Hostmentioning
confidence: 99%
“…The immunocompromised host may also exhibit damaging excess inflammation. HIV-associated immune dysregulation is implicated in acute respiratory distress syndrome in Pneumocystis jirovecii pneumonia (PCP) and also likely contributes to mortality in cryptococcal meningitis [12].…”
Section: The Hostmentioning
confidence: 99%
“…The prognosis of CM remains poor, with a mortality rate of approximately 20% within 3 months of infection, even after standard therapies for the condition have been established 2–4 . In developing countries with limited medical resources, the mortality rate of CM has been reported to be 40%–70% 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In developing countries with limited medical resources, the mortality rate of CM has been reported to be 40%-70%. [5][6][7][8] In general, patients with cryptococcosis are categorized into three groups according to their background and host immune status: patients with HIV, post-organ transplant patients and other patients. 9 Patient background and immune status largely differ between these groups, [10][11][12][13] and several reports have shown that CM in HIV patients has a better prognosis at 3 months than CM in non-HIV patients.…”
Section: Introductionmentioning
confidence: 99%